Broccoli for the brain: a review of the neuroprotective mechanisms of sulforaphane - Bessetti, Riley N.; Litwa, Karen A. (Frontiers in Cellular Neuroscience, 2025)
Sulforaphane, a phytochemical abundant in the sprouts of cruciferous vegetables, protects plants during a critical period of development. Through sulforaphane’s ability to activate the mammalian Nuclear Factor Erythroid 2-related Factor 2 (NRF2) pathway, these beneficial properties extend beyond plants. Our current review explores emerging neuroprotective mechanisms of sulforaphane and their relation to neurological disorders. Primarily, we discuss the ability of sulforaphane to mitigate oxidative stress and prevent neuroinflammation. Given sulforaphane’s ability to activate multiple cytoprotective mechanisms, sulforaphane is emerging as a promising therapeutic for multiple neurodegenerative and neurodevelopmental disorders. In this review, we highlight current clinical trials in neurological disorders and conclude by discussing therapeutic opportunities and challenges for sulforaphane. Together, preclinical models and clinical trials highlight emerging themes of sulforaphane-mediated neuroprotection, including hormetic responses that depend upon the cell/tissue, neurological condition, insult, and developmental stage. In particular, low sulforaphane doses consistently exhibit beneficial effects in preclinical neuronal cell cultures models and avoid cytotoxic effects of higher sulforaphane doses. These factors will be important considerations in informing therapeutic use of sulforaphane.